2012
DOI: 10.1111/j.1477-2574.2012.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Carrier‐bound fibrin sealant compared to oxidized cellulose application after liver resection

Abstract: The results of the present study suggest that the routine use of TachoSil after a liver resection does not reduce the overall complication rate compared with Surgicel application. However, TachoSil may be beneficial in a major hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…For comparison, the perioperative transfusion rate in 133 consecutive liver resection procedures (all types) performed between Nov. 9, 2007, and Nov. 2, 2011, in our institution was 43%. 28 Furthermore, the mean blood loss of 914 mL in the present study is within the range reported by other authors. 16,39,40 …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…For comparison, the perioperative transfusion rate in 133 consecutive liver resection procedures (all types) performed between Nov. 9, 2007, and Nov. 2, 2011, in our institution was 43%. 28 Furthermore, the mean blood loss of 914 mL in the present study is within the range reported by other authors. 16,39,40 …”
Section: Discussionsupporting
confidence: 78%
“…28 Right hepatectomy (odds ratio [OR] 7.8, 95% confidence interval [CI] 2.8-21.2) and repeat hepatectomy (OR 6.1, 95% CI 1.7-21.6) were identified as predictors of blood loss greater than 500 mL in multivariate analysis. For blood loss greater than 1000 mL, only right hepatectomy was a significant risk factor in multivariate analysis (OR 5.6, 95% CI 1.8-16.9).…”
Section: Predictors Of Blood Lossmentioning
confidence: 99%
“…In our study, bleeding after hemostasis and mean first postoperative day blood drainage volume in TachoSil were significantly lower than Surgicel. However, Zacharias and Ferreira [17] found a similar complication rate and mean hospital stay in TachoSil and Surgicel groups; however, TachoSil group had a little higher hospital stay and less major complications. This study did not recognize any of them superior to the other.…”
Section: Discussionmentioning
confidence: 95%
“…The full text of the remaining 33 articles were assessed for eligibility and reviewed in detail: 11 papers were excluded because not pertinent with liver surgery. From 1993 to 2016 we found 22 full‐text article studies , included in this systematic review for qualitative synthesis: among them, 13 combining FMT or MT or FM were included for quantitative meta‐analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%